A rare case of multidrug resistant Leclercia adecarboxylata catheter-related bloodstream infection and an updated brief literature review: Leclercia adecarboxylata catheter-related bloodstream infection. - Colangelo, Cosimo; Tiecco, Giorgio; Di Gregorio, Marco; Capone, Susanna; Allegri, Roberto Luigi; De Francesco, Maria; Caccuri, Francesca; Caruso, Arnaldo; Castelli, Francesco; Focà, Emanuele (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Leclercia adecarboxylata is a gram-negative bacillus, a ubiquitous microorganism, which may be found in both aquatic environments and soil, it was first described by H. Leclerc in 1962 and was reclassified thanks to more sensitive testing methods. L. adecarboxylata has been recently recognized as an emerging pathogen that causes several clinical syndromes not only in immunocompromised patients.